Optimising conservative management of chronic low back pain: study protocol for a randomised controlled trial - Simson, Katherine J; Miller, Clint T; Ford, Jon; Hahne, Andrew; Main, Luana; Rantalainen, Timo; Teo, Wei-Peng; Teychenne, Megan; Connell, David; Trudel, Guy; Zheng, Guoyan; Thickbroom, Gary; et al. (Université d'Ottawa | University of Ottawa, 2017)
Abstract Background Lower back pain is a global health issue affecting approximately 80% of people at some stage in their life. The current literature suggests that any exercise is beneficial for reducing back pain. However, as pain is a subjective evaluation and physical deficits are evident in low back pain, using it as the sole outcome measure to evaluate superiority of an exercise protocol for low back pain treatment is insufficient. The overarching goal of the current clinical trial is to implement two common, conservative intervention approaches and examine their impact on deficits in chronic low back pain. Methods/design Forty participants, 25–45 years old with chronic (>3 months), non-specific low back pain will be recruited. Participants will be randomised to receive either motor control and manual therapy (n = 20) or general strength and conditioning (n = 20) exercise treatments for 6 months. The motor control/manual therapy group will receive twelve 30-min sessions, ten in the first 3 months (one or two per week) and two in the last 3 months. The general exercise group will attend two 1-hour sessions weekly for 3 months, and one or two a week for the following 3 months. Primary outcome measures are average lumbar spine intervertebral disc T2 relaxation time and changes in thickness of the transversus abdominis muscle on a leg lift using magnetic resonance imaging (MRI). Secondary outcomes include muscle size and fat content, vertebral body fat content, intervertebral disc morphology and water diffusion measured by MRI, body composition using dual energy X-ray absorptiometry, physical function through functional tests, changes in corticospinal excitability and cortical motor representation of the spinal muscles using transcranial magnetic stimulation and self-reported measure of pain symptoms, health and disability. Outcome measures will be conducted at baseline, at the 3-month follow-up and at 6 months at the end of intervention. Pain, depressive symptomology and emotions will be captured fortnightly by questionnaires. Discussion Chronic low back pain is ranked the highest disabling disorder in Australia. The findings of this study will inform clinical practice guidelines to assist with decision-making approaches where outcomes beyond pain are sought for adults with chronic low back pain. Trial registration Australian New Zealand Clinical Trials Registry, ACTRN12615001270505 . Registered on 20 November 2015.